2005
DOI: 10.1093/ps/84.6.898
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inorganic and organic selenium sources for broilers

Abstract: An experiment was conducted to compare the effects of organic and inorganic sources of Se on growth performance, carcass traits, breast and plasma Se concentrations, and plasma glutathione peroxidase (pGPX3) activity in broilers. Broiler chicks were sexed on d 0 and within sex, randomly allotted to dietary treatment. Average initial and final BW of the broilers were 47 and 2,684 g, and the experiment lasted 49 d. A 3-phase feeding program similar to industry recommendations was used, and the basal diets for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
110
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(156 citation statements)
references
References 14 publications
43
110
3
Order By: Relevance
“…The values do not prove any significant differences between the groups in the weight of breast and thigh muscle, liver and abdominal fat. The results are in agreement with Downs et al (2000) and Payne and Southern (2005). also reported that vitamin E and Se source at 0.1 ppm did not have a significant influence on eviscerated weight, dressed weight, breast fillet yield or average maryland weight at processing.…”
Section: Statistical Analysessupporting
confidence: 90%
See 1 more Smart Citation
“…The values do not prove any significant differences between the groups in the weight of breast and thigh muscle, liver and abdominal fat. The results are in agreement with Downs et al (2000) and Payne and Southern (2005). also reported that vitamin E and Se source at 0.1 ppm did not have a significant influence on eviscerated weight, dressed weight, breast fillet yield or average maryland weight at processing.…”
Section: Statistical Analysessupporting
confidence: 90%
“…The effects of selenium sources on the performance of broiler chickens, carcass characteristics and meat quality were studied by Echevarria et al (1988), Todorovič et al (1999), Downs et al (2000), Payne and Southern (2005). In the current study of the source of Se at 0.1 ppm did not affect the performance of broilers.…”
mentioning
confidence: 53%
“…A possible reason for the more significant decrease in drip loss by organic Se may be that organic Se was superior to inorganic Se in increasing the antioxidant property of animals. However, Payne and Southern (2005a) reported that the 24 h breast moisture loss of broilers was not affected by Se supplementation (SY or SS) with the basal diet containing 0.12 mg Se/kg. This may be partially due to different Se levels and sources used.…”
Section: Discussionmentioning
confidence: 98%
“…Many of the studies related to organic Se were conducted under normal (Choct et al, 2004;Payne & Southern, 2005) or oxidative stress (Mahmoud & Edens, 2005;Özkan et al, 2007) conditions. Mahmoud & Edens (2005) evaluated the effect of organic Se on performance and different physiological parameters of broilers either in pathogenic Escherichia coli-challenged or under heat-stressed conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Surai (2006) suggested that the growth response of birds to Se supplementation would also depend on the birds' stress level, with stressed birds being more responsive. Some reports (Choct et al, 2004;Payne & Southern, 2005) indicated that dietary supplementation of Se (organic or inorganic) did not affect BW or BWG of broilers reared at optimum (no oxidative stress) conditions. In contrast, organic Se supplementation increased BW of broilers at 42 days of age (Edens, 2001) and improved feed conversion (Naylor et al, 2000) in broilers reared under normal commercial conditions.…”
Section: Resultsmentioning
confidence: 99%